Critical analysis of the pedagogical practice of the teachers trainnees (2013)
This article reports the results of a research project supported by the Research Center of the Universidad Pedagógica Nacional, whose purpose was the redefinition of the training process of the students, in the frame of the pedagogical practice, in one of the research lines for the Degree in Elementary Education with emphasis on Social Sciences. On a theoretical level, analysis and discussion were developed from critical pedagogy, particularly the concepts of pedagogical practice, training and systematization of experiences. Methodologically the project was developed from the Educational Action Research. It was found that students and teachers conceive pedagogical practice in a critical way, related to their reflective and transformative personalities, something that breaks, in some way, with the traditional outlook that defines it as the confirmation of the theory in the field. This way of conceiving is the result of both the training process and the life history of each other, as well as the staging and the discussion of the significance of the practice within the social sciences framework.